Compensating capacitor placement for voltage stability improvement and loss minimization / Hairul Azhar Abdul Manap @ Razak - Abdul Manap @ Razak, Hairul Azhar (1998)
This project discuss on voltage improvement for low voltage distribution system using compensating capacitor method. This method allocates capacitors to certain nodes which are selected by first identifying the branch which has the largest losses. A study is carried out on of a portion of Tenaga Nasional Berhad (TNB) Klang low voltage system. Selection of the area is based on the one that experience voltage drop beyond the tolerable margin. This method is applied to a 42 bus (nodes) low voltage distribution system of 415 V line voltage and 300 kVA of Kampung Perepat Baru, Kapar. This thesis also uses the Distflow load flow technique to compute power flow and voltage profile for radial distribution system